Re-Humanizing Digital Education Through the Integration of Islamic Values and Nature-Based Pedagogy in Indonesia - Yusuf, Iskandar; Nasir, Muhammad; Mahmud, Mochammad Eka (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study addresses the dehumanizing effects of modern digital-age education by examining how Nature Schools (Sekolah Alam) in Indonesia integrate Islamic values with nature-based pedagogy to foster holistic human development. Employing a qualitative multi-site case study design, the research investigated three distinct Nature Schools in East Kalimantan: Balikpapan, Samarinda, and Sangatta. Data were collected through participatory observation, in-depth interviews with principals, teachers, and parents, and documentary analysis of curricula and student portfolios. Analysis followed the interactive model of Miles, Huberman, and Saldaña. The findings reveal three pivotal outcomes. First, the schools successfully deconstruct the science-religion dichotomy by positioning nature as a spiritual laboratory (Ayat Kauniyah) within an integrative curriculum. Second, the internalization of values follows a “Triadic Cycle” comprising transformation (cognitive framing), transaction (dialogical role-modeling), and trans-internalization (reflexive habituation). Third, while this model effectively nurtures holistic student character (Insan Kamil) that values process over mere academic results, a significant external barrier termed the “Laundry Mentality” among parents—a transactional delegation of moral education to the school—creates cognitive dissonance in students and hinders consistent value embodiment. The study concludes that the synthesis of nature-based pedagogy and Islamic values presents a viable, non-dichotomous model for re-humanizing education. However, its success is contingent upon overcoming sociological barriers through active family-school partnership, suggesting that educational transformation must extend beyond school walls to include the domestic ecosystem.